Métodos eletroanalíticos e cromatográficos aplicados na análise de corantes usados como marcadores em combustíveis - Trindade, Magno Aparecido Gonçalves [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
Neste trabalho é mostrado o desenvolvimento de diferentes métodos analíticos para quantificação dos corantes Quinizarina (QNZ), Solvente Azul 14 (SB-14), Solvente Azul 35 (SB-35), Solvente Laranja 7 (SO-7) e Solvente Vermelho 24 (SR-24) usados como marcadores em combustíveis. Inicialmente, estudou-se o comportamento voltamétrico dos corantes QNZ e SB-14 sobre eletrodo de carbono vítreo em meio misto de tampão Britton- Robinson/acetonitrila (7:3, v/v) e Britton-Robinson/dimetilformamida (1:1, v/v), respectivamente. Os resultados obtidos mostraram que a oxidação da QNZ ocorre em +0,47 V vs. Ag/AgCl e a redução do corante SB-14 em -0,40 V vs. Ag/AgCl, cujo processo apresenta fortes evidências de um transferência eletrônica reversível, mas complicado por reações químicas acopladas e por adsorção. A voltametria de onda quadrada (VOQ) apresentou desempenho analítico superior às demais técnicas eletroquímicas com limite de detecção da ordem de 4,00×10-7 mol L-1 (QNZ) e 3,00×10-7 mol L-1 (SB-14), além de propiciar um menor tempo de análise. Os métodos eletroanalíticos desenvolvidos acoplados a etapas prévias de extração desses corantes em matrizes como gasolina, querosene e óleo diesel forneceram resultados satisfatórios com valores de eficiência de extração entre 90,0 e 94,0% (QNZ) e entre 87,0 e 98,0% (SB-14), respectivamente. A redução desses corantes também foi monitorada sobre eletrodos de carbono impressos em meio de tampão Britton- Robinson/dimetilformamida (7:3, v/v) visando desenvolver novos métodos de análise. Os resultados foram adaptados ao novo sistema usando surfactante aniônico dioctil sulfosuccinato de sódio (DSS) e catiônico brometo de cetiltrimetilamônio (CTAB) para melhorar a solubilidade dos corantes e aumentar a durabilidade desses eletrodos na presença de solventes orgânicos. Curva analítica no intervalo...

In the present work the development of different analytical methods to quantify the dyes Quinizarine (QNZ), Solvent Blue 14 (SB-14), Solvent Blue 35 (SB-35), Solvent Orange 7 (SO-7) and Solvente Red 24 (SR-24) used as marker in fuels are showed. Firstly, the voltammetric behavior for the dyes QNZ and SB-14 was studied onto glassy carbon electrode surface in a mixture of Britton-Robinson buffer with acetonitrile (7:3, v/v) and in a mixture of Britton-Robinson buffer with N, N-dimethylformamide (1:1, v/v), respectively. The obtained results showed that the oxidation of the QNZ occur at +0.47 V vs. Ag/AgCl and the reduction of the SB-14 occur at -0.40 V vs. Ag/AgCl, which the electrodic process was reversible, but complicated by coupled to chemical reactions and for the adsorption phenomenon. The square-wave voltammetry (SWV) presented analytic performing superior than the other electroanalytical techniques with detection limit around of 4.00×10-7 mol L-1 (QNZ) and 3.00×10-7 mol L-1 (SB-14), besides propitiating a smaller time of analysis. The developed electroanalytical methods coupled with suitable sample pretreatment protocols steps for the extraction of the dyes in fuel samples such as, gasoline, kerosene and diesel oil provide satisfactory results with recovery values between 90.0 and 94.0% (QNZ) and between 87.0 and 98.0% (SB-14), respectively. The reduction of these dyes was also studied onto screenprinted carbon electrode (SPCE) surface in a mixture of Britton-Robinson buffer and N,Ndimethylformamide (7:3, v/v) with the objective to develop new electroanalytical methods. The results were adapted to the new system using anionic Dioctyl sulfosuccinate sodium (DSS) and cationic cetyltrimethylammonium bromide (CTAB) surfactants to improve the dyes solubility and to increase the durability of the electrodes in medium containing organic solvents. Analytical curve in the range... (Complete abstract click electronic access below)
Keywords: Quimica analitica; Eletroanalítica; Eletroquimica; Combustiveis; Analytical chemistry